If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1(2x + 7) = 13x + -5(x + -7) Reorder the terms: 12 + -1(7 + 2x) = 13x + -5(x + -7) 12 + (7 * -1 + 2x * -1) = 13x + -5(x + -7) 12 + (-7 + -2x) = 13x + -5(x + -7) Combine like terms: 12 + -7 = 5 5 + -2x = 13x + -5(x + -7) Reorder the terms: 5 + -2x = 13x + -5(-7 + x) 5 + -2x = 13x + (-7 * -5 + x * -5) 5 + -2x = 13x + (35 + -5x) Reorder the terms: 5 + -2x = 35 + 13x + -5x Combine like terms: 13x + -5x = 8x 5 + -2x = 35 + 8x Solving 5 + -2x = 35 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 5 + -2x + -8x = 35 + 8x + -8x Combine like terms: -2x + -8x = -10x 5 + -10x = 35 + 8x + -8x Combine like terms: 8x + -8x = 0 5 + -10x = 35 + 0 5 + -10x = 35 Add '-5' to each side of the equation. 5 + -5 + -10x = 35 + -5 Combine like terms: 5 + -5 = 0 0 + -10x = 35 + -5 -10x = 35 + -5 Combine like terms: 35 + -5 = 30 -10x = 30 Divide each side by '-10'. x = -3 Simplifying x = -3
| 1x-8=3x-12 | | YoverZ=8 | | 0-3=0 | | 4x-3+x=7 | | 16/32=(12-x)/x | | 21x+8=11x | | 5z+4=10 | | -3.6k-1.7=27.82 | | x-2-(x-8)=4x+6 | | -3.6k-1.7=2 | | 18a-12=24a+16 | | K/-3-11=-2 | | Z^2=-16-30i | | C=8/3(k-19) | | 2x-6=x-1/2 | | 4x+32=64y | | x-6/2=1-x/6 | | 9x-30=5x+10 | | 10+6(-9-4x)=10(x-12)+8 | | Y/z=8 | | -8(3-t)=32 | | 2x+50=4x-12 | | 11/4=77/x | | f(x)=12x+17 | | 2x+2x-20+x=180 | | 5/9=55/x | | -3+4=0 | | 3x+88=128-7x | | 3-1.3x=1/6x | | 8x+2(x+8)=6 | | 11r+19-6+11=4+10r | | (16.3180387-a)(16.3180387-b)=0 |